2019
DOI: 10.3758/s13414-019-01756-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arousal on biased competition in attention and short-term memory

Abstract: A recent theory proposes that arousal amplifies the competition between stimulus representations, strengthening already strong representations and weakening already weak representations in perception and memory. Here, we report a stringent test of this arousal-biased competition theory in the context of visual attention and short-term memory. We examined whether pre-trial arousal enhances the bottom-up attentional bias toward physically salient versus less salient stimuli in a multi-letter identification task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(86 reference statements)
2
6
0
Order By: Relevance
“…Based on the results of Lee et al ( 2012 ) and Sutherland and Mather ( 2018 ) arousal only has a facilitating effect for targets with high but not low physical salience. In contrast, Ásgeirsson and Nieuwenhuis ( 2017 , 2019 ) found no behavioral effects of the arousal manipulation across five experiments, although arousing pictures caused significant LLP modulation (400–600 ms and 800–1200 ms) per the EEG results.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Based on the results of Lee et al ( 2012 ) and Sutherland and Mather ( 2018 ) arousal only has a facilitating effect for targets with high but not low physical salience. In contrast, Ásgeirsson and Nieuwenhuis ( 2017 , 2019 ) found no behavioral effects of the arousal manipulation across five experiments, although arousing pictures caused significant LLP modulation (400–600 ms and 800–1200 ms) per the EEG results.…”
Section: Resultsmentioning
confidence: 81%
“…I found five studies where the task-irrelevant emotional stimuli preceded the presentation of the task , in all cases visual search paradigms were used. Four studies used visual stimuli (IAPS pictures) to elicit emotional arousal (Ásgeirsson & Nieuwenhuis, 2017 , 2019 ; Lee et al, 2012 ; Zsido et al, 2019b ). Auditory stimuli were used in one study (Sutherland & Mather, 2018 ) and one experiment (Ásgeirsson & Nieuwenhuis, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dwell time is also longer for high arousal pictures with the length of dwell time being related to changes in pupil dilations (Astudillo et al, 2018). Interestingly, two studies have also revealed no behavioral effects of increased arousal despite showing significant changes in the late positive potential component of event-related potentials that indicate an electrophysiological arousal response (Ásgeirsson & Nieuwenhuis, 2017(Ásgeirsson & Nieuwenhuis, , 2019. These conflicting findings in the literature in addition to our divergent results from two unique search paradigms emphasize the importance of understanding why arousal does or does not modulate attention processing in specific task conditions and understanding the mechanisms underlying interactions between networks of arousal and each cognitive process.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been proposed that instead of stimulus valence, arousal properties of the stimulus influence WM performance. In their arousal-biased competition (ABC) model, Mather & Sutherland (2011) propose that arousal amplifies the effects of competition between stimuli such that the processing of high priority stimuli is improved and the processing of low priority stimuli is weakened (but see Ásgeirsson & Nieuwenhuis, 2019). They also propose that Mather and colleagues' findings that VSWM for negative pictures is poorer than for neutral pictures (Mather et al, 2006;Mitchell et al, 2006) are consistent with the ABC theory.…”
Section: Introductionmentioning
confidence: 86%